We are all equal - Prysak, Dorota; Orządała, Olimpia (No Limits, 2024)
The article addresses the issue of social inclusion of people with disabilities, especially intellectual disabilities, and the role played by teachers and special education teachers in this process. It highlights the challenges and opportunities associated with educational and social work with people with diverse needs. The text draws attention to the need to overcome mental barriers, use simple language in communication, and listen carefully when interacting with people with intellectual disabilities. Working with people with intellectual disabilities can be not only an important professional experience but also a source of deep reflection and personal development. The article emphasises that the basis for effective support is the recognition of the equality and dignity of every human being.